Fluorine-free filtering material with high water resistance and durability and preparation method thereof
By using the waterproofing agent obtained by the cross -linking monomer polymerization in the fluorine -free filtration material, the three -dimensional mesh structure is formed, and the problem of insufficient waterproofing and poor durability of the existing materials is solved. Filter material.
Patent Information
- Application Number
- CN202411609458.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
AI Technical Summary
Existing fluorine-free filter materials show insufficient waterproofness and poor durability in practical applications, which cannot meet the needs of use.
The cross -linked monomer aggregation of the cross -linking monomer containing the formula (Ⅰ), (Ⅱ), (Ⅲ), (ⅲ), and (ⅳ) is used to prepare fibrous substrates through wet papermaking process, combined with binders to form a three -dimensional network The shape of the waterproof layer and the fiber substrate enhance the intensity of the waterproof layer.
A fluorine -free filtering material with high water resistance and durability has good waterproof performance and mechanical stability, and can maintain a long waterproof effect in complex environments.
Smart Images

Figure BDA0005130565230000021 
Figure BDA0005130565230000071 
Figure BDA0005130565230000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, and in particular to a fluorine-free filter material with high water resistance and durability and a preparation method thereof. Background Art
[0002] In some highly targeted industries, filter materials are required to have certain waterproof and moisture-proof properties. In the prior art, fluorine-containing waterproofing agents are usually used to treat fiber substrates, etc., so that a waterproof coating is formed on the outside of the fiber, thereby obtaining filter materials with waterproof effects. However, some fluorides in fluorine-containing waterproofing agents, such as perfluorooctane sulfonate (PFOS) and perfluorooctyl sulfide (PFOA), etc., pose potential risks to the environment and human health. Many countries have banned or restricted the use of fluorine-containing waterproofing agents.
[0003] Silicone waterproofing agents are not easy to deposit in organisms and are easy to degrade. They are safer and more environmentally friendly fluorine-free waterproofing agents. Chinese patent CN103243612B discloses a highly water-resistant nuclear-grade glass fiber air filter paper, which is made of alkali-free glass fibers with diameters of 0.1-0.3 μm, 0.5-0.7 μm and 0.8-1.0 μm and alkali-free glass long fibers with diameters of 1.4-1.6 μm, and a water-resistant layer attached to the surface of the filter paper composed of hydrogen-containing silicone oil and acrylic emulsion. The filter paper has a much longer hydrostatic pressure resistance (>8 kPa) and water resistance time (48 hours) than ordinary waterproof filter paper.
[0004] Chinese patent application CN110387062A discloses a super oleophilic and super hydrophobic sponge for oil-water separation. An organic dispersion of nano-silica and MQ silicone resin is coated on the surface of the sponge by dip coating. After the solvent evaporates, the MQ silicone resin and nano-silica are deposited on the surface of the sponge, giving the sponge super hydrophobic properties, and the contact angle with aqueous substances reaches 151.7° to 155.6°.
[0005] Yuan Chengce et al. used ammonia water as catalyst to prepare methyl silicone resin sol, and then used the silicone resin sol to infiltrate filter paper to form a hydrophobic filter material with a surface composed of non-polar groups (Yuan Chengce, Zhang Qun, Dong Wei, et al. Preparation of oil-water separation materials using silicone-modified filter paper. [J] Chemistry and Adhesion, 2014, 36: 4246-250). The macroscopic hydrophobicity and lipophilicity test results of the hydrophobic filter material were good.
[0006] The above three solutions all use silicone waterproofing agents to construct a waterproof layer on the surface of the substrate, and the hydrophobic test results are good. However, in actual application, the above filter materials show problems such as insufficient waterproofness and poor durability, and can no longer meet the use requirements.
[0007] Therefore, it is urgent to provide a new type of fluorine-free filter material in order to solve the above technical problems. Summary of the invention
[0008] The object of the present invention is to provide a fluorine-free filter material with high water resistance and durability and a preparation method thereof in view of the above problems.
[0009] In order to achieve its purpose, the present invention adopts the following technical solution:
[0010] The first aspect of the present invention provides a highly water-resistant and durable fluorine-free filter material, wherein the components of the fluorine-free filter material include, by mass percentage, 77.0 to 96.8 wt% glass fiber, 0 to 12.0 wt% organic synthetic fiber, 3.0 to 9.5 wt% binder, and 0.2 to 1.5 wt% waterproofing agent;
[0011] Wherein, the waterproofing agent comprises structural fragments represented by formula (I), (II), (III) and (IV):
[0012]
[0013] In formula (I), (II), (III) and (IV), R is selected from one or more of hydrogen, hydroxyl, saturated group and unsaturated group; R' is selected from one or more of hydrogen, saturated group and unsaturated group, and the position of R' is a group or a chemical bond, and the chemical bond bonds the oxygen atom to any of the fragments of formula (I), (II), (III) and (IV).
[0014] The saturated groups include: C1-C10 branched or straight chain alkyl groups, C3-C6 cycloalkyl groups, C1-C10 branched or straight chain alkoxy groups;
[0015] Preferably, the saturated group is a C1-C6 branched or straight-chain alkyl group, a C1-C6 branched or straight-chain alkoxy group, and further preferably, the saturated group is selected from methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), methoxy (-OCH3), ethoxy (-OCH2CH3);
[0016] The unsaturated groups include: C2-C10 branched or straight-chain alkenyl, C2-C10 branched or straight-chain alkynyl, C1-C10 branched or straight-chain acyl, C1-C10 branched or straight-chain acyloxy, phenyl, carboxyl, aldehyde;
[0017] Wherein, the C1-C10 branched or straight-chain acyl / acyloxy group refers to: in the acyl / acyloxy group, except for the carbonyl (-C=O) / -COO, the remaining part is hydrogen (i.e., formyl, formyloxy), branched or straight-chain alkyl, branched or straight-chain alkenyl, branched or straight-chain alkynyl;
[0018] Preferably, the unsaturated group is a C2-C6 straight-chain alkenyl group or a C2-C6 straight-chain alkynyl group; further preferably, the unsaturated group is a vinyl group (-CH=CH2) or an ethynyl group (-C≡CH).
[0019] Preferably, among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragment of formula (I) is 12.11% to 20.33%, the content of the fragment of formula (II) is 49.93% to 73.50%; the content of the fragment of formula (III) is 5.10% to 29.27%; the content of the fragment of formula (IV) is 0.85% to 9.92%;
[0020] Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragments containing saturated groups is 61.46% to 70.91%; the content of the fragments containing unsaturated groups is 27.94% to 30.29%.
[0021] Further preferably, among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragment of formula (I) is 17.11% to 17.22%, the content of the fragment of formula (II) is 63.91% to 65.81%; the content of the fragment of formula (III) is 14.02% to 14.63%; the content of the fragment of formula (IV) is 2.34% to 4.96%;
[0022] Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragments containing saturated groups is 66.84% to 68.62%; the content of the fragments containing unsaturated groups is 28.20% to 29.04%.
[0023] In the above technical solution, the waterproofing agent is obtained by polymerizing a cross-linking monomer A, a cross-linking monomer B, a cross-linking monomer C, and a cross-linking monomer D, and the cross-linking monomer A, the cross-linking monomer B, the cross-linking monomer C, and the cross-linking monomer D respectively contain structural fragments represented by formulas (I), (II), (III), and (IV).
[0024] Preferably, the crosslinking monomer A is trimethylethoxysilane, the crosslinking monomer B is dimethyldiethoxysilane, the crosslinking monomer C is vinyltriethoxysilane, and the crosslinking monomer D is tetraethoxysilane.
[0025] When preparing the waterproofing agent, the molar ratio of the crosslinking monomer A, the crosslinking monomer B, the crosslinking monomer C and the crosslinking monomer D is 10-17.5:29-41:2-14:0.5-4, preferably 10.3-17.2:29-41:2.5-14:0.5-3.5 or 13-15:36-37:6-7:1.5-2.0.
[0026] Preferably, the glass fiber is selected from micro glass fiber wool and glass fiber chopped strands;
[0027] The organic synthetic fiber is selected from one or more of polypropylene fiber, polyester fiber, polyacrylonitrile fiber, polyamide fiber, polyimide fiber, and aramid fiber;
[0028] The binder is selected from one or more of acrylic acid, polyurethane, vinyl acetate, and aluminum silicate;
[0029] The fiber diameter of the micro glass fiber cotton is 0.1 to 5 μm, the fiber diameter of the glass fiber chopped strands is 5 to 10 μm; the fiber diameter of the organic synthetic fiber is 0.5 to 20 μm;
[0030] The gram weight of the fluorine-free filter material is 10 to 200 g / m 2 ; Thickness is 0.1~10mm.
[0031] Preferably, the components of the fluorine-free filter material include, by mass percentage, 94.0-95.5wt% glass fiber, 4.0-5.0wt% binder and 0.5-1.0wt% waterproofing agent;
[0032] In the glass fiber, the mass ratio of micro glass fiber wool with a diameter of 0.1 to 2 μm, micro glass fiber wool with a diameter of 2 to 5 μm, and glass fiber chopped strands is 4.5 to 5.5:1.5 to 2.5:1, preferably 5:2:1;
[0033] The gram weight of the fluorine-free filter material is 67.27-73.82 g / m 2 ; Thickness is 0.45~0.55mm.
[0034] The second aspect of the present invention provides a method for preparing the fluorine-free filter material described in any one of the above, comprising the following steps:
[0035] S1. Select fiber raw materials according to proportion and prepare fiber substrate by wet papermaking process;
[0036] S2, select waterproofing agent and adhesive in proportion and mix them evenly to prepare an aqueous solution with a concentration of 0.5-1wt%, which is a glue solution;
[0037] S3, dipping or spraying the adhesive solution on the fiber substrate to obtain adhesive paper;
[0038] S4. Dry the adhesive paper at a temperature of 100-120° C., and cure it at a temperature of 150-300° C. for 10-30 minutes to obtain a fluorine-free filter material.
[0039] In the technical solution of the preparation method of the fluorine-free filter material, the waterproofing agent is prepared by cross-linking and polymerizing monomers containing structural fragments represented by formula (I), (II), (III), and (IV). The preparation method of the waterproofing agent comprises the following steps:
[0040] Step A: Select a cross-linking monomer emulsion in proportion and place it in a reaction container, keep stirring at room temperature (20-25° C.), add 1-5% (based on the amount of monomer substance) of 10% dilute hydrochloric acid by mass, and stir at room temperature (20-25° C.) for 1-2 hours after the addition is completed to obtain a silanol solution;
[0041] Step B: Add 5-10% (based on the mass fraction of monomers) of surfactant and 1-5V of deionized water into the reaction container, stir, add the above-mentioned silanol solution dropwise while maintaining room temperature, then heat to 80-120°C to react for 5-8h, cool naturally to room temperature, add 10-20% NaOH solution by mass to adjust the pH value to neutral, filter, and obtain a silicone waterproofing agent.
[0042] The beneficial effects of the present invention are:
[0043] In the present invention, the waterproof layer of the fluorine-free filter material is formed by cross-linking the fragments represented by formula (I), (II), (III), and (IV), and has a three-dimensional network structure, wherein the Si-O bond has a strong polarity and tends to gather inside the network structure, and the saturated groups in R and R' form a compact hydrophobic layer as hydrophobic groups, giving the filter material good waterproof performance, and the hydrogen, hydroxyl, and unsaturated groups in the structure participate in the formation of chemical bonds (such as Si-C bonds, etc.), so that the organosilicon waterproof agent can be stably combined with the fiber and the binder, and is not easy to fail and break, thereby improving the bonding strength of the waterproof agent with the fiber substrate and the binder, and having strong durability. The organosilicon waterproof agent of the present invention does not contain fluorine element, is environmentally friendly and non-toxic, and is harmless to the human body. The hydrophobic layer structure formed is compact, and the prepared filter material has good waterproof performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 These are the failure test results of the example samples and the comparative example samples.
[0045] Figure 2 It is the hydrophobic effect result of the sample of Example 1 and the comparative sample after multiple friction cycles. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.
[0047] The experimental methods in the following examples are conventional methods unless otherwise specified.
[0048] The raw materials trimethylethoxysilane (CAS No. 1825-62-3), dimethyldiethoxysilane (CAS No. 78-62-6), vinyltriethoxysilane (CAS No. 78-08-0), and tetraethoxysilane (or ethyl orthosilicate, CAS No. 78-10-4) are all purchased from commercial sources.
[0049] The method for preparing the highly water-resistant and durable fluorine-free filter material of the present invention is carried out according to the following steps:
[0050] S1. Prepare fiber raw materials: select fiber substrates used as raw materials in proportion, the fiber substrates including 85-100wt% glass fibers and 0-15wt% organic synthetic fibers, wherein the glass fibers are selected from micro glass fiber cotton (preferably with a fiber diameter of 0.1-2μm, 2-5μm) and chopped glass fibers (preferably with a fiber diameter of 5-10μm); the organic synthetic fibers are selected from one or more of polypropylene fibers, polyester fibers, polyacrylonitrile fibers, polyamide fibers, polyimide fibers, and aramid fibers, and the fiber diameter of the organic synthetic fibers is 0.5-20μm.
[0051] S2. Preparation of wet paper: Take the prepared fiber substrate, disperse it in water with a fiber deflagrator, add a dispersant (dilute acid can be used, preferably a sulfuric acid solution with a mass concentration of 10%) to adjust the pH value to 2-3 to disperse the glass fiber; beat and disperse to obtain a slurry, add water to adjust the slurry concentration to 0.05-3wt%, and shape it with a papermaking sheeter to obtain wet paper.
[0052] S3. Preparation of glue solution: waterproofing agent and adhesive are selected in proportion and mixed evenly, and water is added to dilute and prepare an aqueous solution with a concentration of 0.5-1wt%, which is the glue solution.
[0053] Among them, the auxiliary agent includes 5-25wt% waterproofing agent and 75-95wt% binder, and the waterproofing agent is obtained by mixing and cross-linking polymerization of four cross-linking monomers: trimethylethoxysilane (cross-linking monomer A), dimethyldiethoxysilane (cross-linking monomer B), vinyltriethoxysilane (cross-linking monomer C), and tetraethoxysilane (cross-linking monomer D).
[0054] The binder is selected from one or more of acrylic acid, polyurethane, vinyl acetate, and aluminum silicate.
[0055] S4. Applying glue solution: soaking the wet paper in the glue solution, or spraying the glue solution evenly on the surface of the wet paper to obtain glued paper.
[0056] In this step, the glue solution can be directly sprayed on the wet paper, or the wet paper can be immersed in the glue solution to apply glue. Both methods are acceptable, as long as the paper absorbs and adheres to the corresponding mass percentage (see the glue percentage in Table 2) of the auxiliary glue. The mass percentage of the fiber substrate in the fluorine-free filter material of the present invention is 89-96.5% (preferably 94-95.5% or 94.5-95.2% or 94.9-95.0%), and the remainder is the auxiliary agent.
[0057] S5, drying the adhesive tape at a temperature of 100-120° C. for 5-10 min, and then curing at 150-300° C. for 10-30 min to obtain the fluorine-free filter material of the present invention.
[0058] In step S3, the preparation method of the waterproofing agent is performed according to the following steps:
[0059] Step A: Select a cross-linking monomer emulsion in proportion and place it in a reaction container, keep stirring at room temperature (20-25° C.), add 1-5% (based on the amount of monomer substance) of 10% dilute hydrochloric acid by mass, and stir at room temperature (20-25° C.) for 1-2 hours after the addition is completed to obtain a silanol solution;
[0060] Step B: Add 5-10% (based on the mass fraction of monomers) of surfactant and 1-5V of deionized water into the reaction container, stir, add the above-mentioned silanol solution dropwise while maintaining room temperature, then heat to 80-120°C to react for 5-8h, cool naturally to room temperature, add 10-20% NaOH solution by mass to adjust the pH value to neutral, filter, and obtain a cross-linked silicone waterproofing agent.
[0061] The amount of dilute hydrochloric acid used is preferably 2-3% of the amount of the monomer substance, the deionized water is preferably 3 times the volume of the monomer, and the amount of the surfactant used is preferably 6% of the mass fraction of the monomer.
[0062] The surfactant is selected from cationic surfactants or nonionic surfactants, preferably nonionic surfactants.
[0063] Cationic surfactants include hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dioctadecyldimethylammonium chloride, dodecylbenzyldimethylammonium chloride, octadecylbenzyldimethylammonium chloride, and the like.
[0064] The nonionic surfactants include: fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, sorbitan fatty acid ester, sorbitan polyoxyethylene ether ester, glycerol monostearate, etc. The preferred surfactant is fatty alcohol polyoxyethylene ether, and more preferably caprylic acid polyoxyethylene ether.
[0065] After the waterproofing agent is prepared, part of the water can be evaporated or diluted with water according to the use requirements to adjust the solid content of the emulsion to the required level.
[0066] In the present invention, hydrochloric acid is used as an acid catalyst in the hydrolysis process to promote the full hydrolysis of the cross-linked monomers, so that the monomers are converted into hydroxyl-containing silanols. During the heating polymerization process, a silanol condensation reaction occurs to form a silicon-oxygen-silicon (Si-O-Si) bond, thereby constructing a three-dimensional network structure; the surfactant can enhance the electrolyte stability of the emulsion and help maintain the stability during and after the emulsion polymerization; dilute hydrochloric acid and NaOH solution can adjust the pH value of the reaction system, but it should be understood that the present invention does not have any restrictions on the type of pH adjuster. In other embodiments, other reagents such as sulfuric acid, acetic acid, and ammonia water can also be used.
[0067] The gram weight of the fluorine-free filter material prepared by the method of the present invention is 10 to 200 g / m 2 , preferably 67.27~73.82g / m 2 ; The thickness is 0.1-10mm, preferably 0.45-0.55mm; the hydrostatic pressure resistance is >5kPa, preferably 9.46-10.33kPa; the failure time is >48h, that is, the waterproof layer retention rate within 48h is >80%, preferably the failure time is >168h, and the waterproof layer retention rate is 85-95%; more preferably, the waterproof layer retention rate within 168h is 85.29-90.92%; the resistance is 50-500Pa, preferably 268-276Pa.
[0068] In the preparation method of the above fluorine-free filter material, glass fiber and organic synthetic fiber are used to prepare the fiber substrate, and a filter material with good waterproof effect is obtained by applying a glue solution containing a waterproof agent. It should be understood that the above preparation method is only a preferred preparation method of the present invention, and the material used for the fiber substrate is not limited thereto. In other embodiments of the present invention, natural fibers (such as cotton fibers, wool fibers, wood pulp fibers), inorganic fibers (such as ceramic fibers) and other materials can also be used to prepare the fiber substrate.
[0069] Similarly, the gram weight, thickness, hydrostatic pressure resistance, failure time, waterproof layer retention rate, resistance and other related data of the present invention are also obtained based on the substrate prepared from glass fiber and organic synthetic fiber. When other fiber substrate raw materials are used, the values of various data will change accordingly depending on the type of raw materials, thereby exceeding the above range, but it does not mean that the waterproofing agent provided by the present invention cannot be applied to the substrate.
[0070] In the above preparation method, trimethylethoxysilane (cross-linking monomer A), dimethyldiethoxysilane (cross-linking monomer B), vinyltriethoxysilane (cross-linking monomer C), and tetraethoxysilane (cross-linking monomer D) are used as raw monomers to prepare a waterproofing agent, wherein the cross-linking monomer A contains the structural fragment shown in formula (I), the cross-linking monomer B contains the structural fragment shown in formula (II), the cross-linking monomer C contains the structural fragment shown in formula (III), and the cross-linking monomer D contains the structural fragment shown in formula (IV).
[0071]
[0072] It should be noted that the above-mentioned monomer raw material is only one embodiment of the present invention, and according to actual needs, monomer raw materials containing other groups can also be selected.
[0073] In some embodiments, the crosslinking monomer may have one or more groups such as hydrogen, hydroxyl, methyl, ethyl, n-propyl, isopropyl, methoxy, ethoxy, phenyl, vinyl, ethynyl, formyl, formyloxy, acetoxy, carboxyl, aldehyde, etc., for example: dimethyldimethoxysilane, diphenyldimethoxysilane, methylphenyldiethoxysilane, di-p-tolyldimethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, tetramethoxysilane, trimethylsilanol, triethylsilanol, tripropylsilanol, trimethoxysilanol, triethoxysilanol, dimethylvinylsilanol, dimethylphenylsilanol, dimethylsilanediol, diethylsilanediol, dipropylsilanediol, vinyltrisilanol, orthosilicic acid, etc.
[0074] In other embodiments, the cross-linking monomer may also be a partially cross-linked oligomer, such as octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, octaphenylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, and the like.
[0075] Specifically, in formula (I), (II), (III), and (IV), R can be selected from one or more of hydrogen, hydroxyl, saturated group, and unsaturated group, R' can be selected from one or more of hydrogen, saturated group, and unsaturated group, and the position of R' can also be not a group, but a chemical bond, which can make the oxygen atom bond with any fragment of formula (I), (II), (III), and (IV). The fragments shown in formula (I), (II), (III), and (IV) are cross-linked with each other, wherein preferably, Si-O bonds are formed. Taking formula (IV) as an example, Si is connected to O of other fragments on the left side, and O is connected to Si of other fragments on the right side. When the position of R' is a chemical bond, it is preferably connected to Si in other fragments, that is, Si-O-Si bonds are formed between the two fragments, so as to form a three-dimensional cross-linked network structure.
[0076] The saturated group refers to a group without unsaturated bonds (ie, the number of unsaturated bonds in the group is 0). The saturated group includes: C1-C10 branched or straight-chain alkyl groups, C3-C6 cycloalkyl groups, and C1-C10 branched or straight-chain alkoxy groups.
[0077] Preferably, the saturated group is a branched or straight-chain alkyl group of C1 to C6, or a branched or straight-chain alkoxy group of C1 to C6, such as: methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), methoxy (-OCH3), ethoxy (-OCH2CH3), etc.
[0078] An unsaturated group refers to a group containing at least one unsaturated bond, and the unsaturated groups include: C2-C10 branched or straight-chain alkenyl, C2-C10 branched or straight-chain alkynyl, C1-C10 branched or straight-chain acyl, C1-C10 branched or straight-chain acyloxy, phenyl, carboxyl, aldehyde, etc.
[0079] The branched or straight-chain acyl / acyloxy group of C1 to C10 means that in the acyl / acyloxy group, except for the carbonyl group (-C=O) / -COO, the remaining part is hydrogen (i.e. formyl, formyloxy), branched or straight-chain alkyl, branched or straight-chain alkenyl, branched or straight-chain alkynyl.
[0080] Preferably, the unsaturated group is a C2-C6 straight-chain alkenyl group, a C2-C6 straight-chain alkynyl group, such as vinyl (-CH=CH2), ethynyl (-C≡CH), and the like.
[0081] One or more hydrogen atoms in the above-mentioned hydrocarbon groups (alkyl, cycloalkyl, alkenyl, alkynyl, phenyl) and alkoxy and acyloxy groups can be substituted, wherein the substituent group can be a group without unsaturated bonds, such as halogen, hydroxyl, amine, etc., or a group containing unsaturated bonds, such as carboxyl, aldehyde, amide, nitrile, etc.
[0082] The group formed after substitution is classified into the above-mentioned saturated group and unsaturated group according to the number of unsaturated bonds. Preferably, the substituted group is a carboxyl group, such as carboxymethyl (-CH2COOH), carboxyethyl (-CH2CH2COOH), etc.
[0083] Among all the fragments represented by formula (Ⅰ), (Ⅱ), (Ⅲ) and (Ⅳ), the content of the fragment of formula (Ⅰ) is 12.11% to 20.33%, and the preferred content is 17.11% to 17.22%; the content of the fragment of formula (Ⅱ) is 49.93% to 73.50%, and the preferred content is 63.91% to 65.81%; the content of the fragment of formula (Ⅲ) is 5.10% to 29.27%, and the preferred content is 14.02% to 14.63%; the content of the fragment of formula (Ⅳ) is 0.85% to 9.92%, and the preferred content is 2.34% to 4.96%.
[0084] Among all the fragments represented by formula (I), (II), (III) and (IV), the content of fragments containing saturated groups is 61.46% to 70.91%, and the preferred content is 66.84% to 68.62%; the content of fragments containing unsaturated groups is 27.94% to 30.29%, and the preferred content is 28.20% to 29.04%.
[0085] In the present invention, a waterproofing agent is mixed with a binder, and the mixed auxiliary agent is used to treat the fiber substrate, so that the filter material obtains a good waterproofing effect. The weight of the waterproofing agent accounts for 5-25wt% of the weight of the auxiliary agent, preferably, the weight of the waterproofing agent accounts for 13.6wt% of the weight of the auxiliary agent, and the remainder is the binder.
[0086] In the fluorine-free filter material of the present invention, the waterproof layer has structural fragments shown in formulas (I), (II), (III) and (IV), the saturated groups in the fragments have a hydrophobic function, and the unsaturated groups form a chemical bond between the waterproof layer and the fiber substrate. By adjusting the content of the fragments containing saturated and unsaturated groups, the hydrophobic property of the waterproof layer and the bonding strength with the substrate can be regulated; the structural fragments shown in formulas (I), (II), (III) and (IV) in the waterproof layer form a three-dimensional network structure, and the fragments of formulas (II) and (III) constitute the main components of the network structure. This structure can make the waterproof layer structure on the surface of the fiber substrate complete and durable, and keep the hydrophobic property of the waterproof layer consistent and the hydrophobic effect good.
[0087] It should be understood that the performance of the waterproof layer of the filter material of the present invention is controlled by the content of each of the above-mentioned fragments. On the basis of maintaining the content of each fragment, different waterproofing agent monomer raw materials can be selected according to actual needs to change the type of groups in the fragment.
[0088] Application Examples
[0089] The fluorine-free filter materials of Examples 1-9 and Comparative Examples 1-2 were prepared according to the above method. The raw materials and proportions used are shown in Table 1-2.
[0090] Table 1 Composition of additives
[0091]
[0092]
[0093] Table 2 Ratio of raw materials in filter materials
[0094]
[0095] *Note: In Table 2, the fiber substrate ratio refers to the mass percentage of the fiber raw material in the final filter material product, and the glue ratio refers to the mass percentage of auxiliary agents such as waterproofing agent and adhesive in the final filter material product.
[0096] The experimental settings of Examples 1-9 and Comparative Examples 1-2 are summarized as follows:
[0097] Example 1: The filter material does not contain inorganic fibers, the glue accounts for about 5%, the mass of the binder is about 6 to 6.5 times the mass of the waterproofing agent, and the content of the fragment of formula (II) is about 4.5 times the content of the fragment of formula (III).
[0098] Example 2: Compared with Example 1, the waterproofing agent composition is changed to reduce the content of the fragment of formula (II) and increase the content of the fragment of formula (III), while the rest remain unchanged.
[0099] Example 3: Compared with Example 1, the waterproofing agent composition is changed to increase the content of the fragment of formula (II) and reduce the content of the fragment of formula (III), while the rest remain unchanged.
[0100] Embodiment 4: Compared with Embodiment 1, the amount of glue applied is reduced so that the glue accounts for about 4%, and the rest remain unchanged.
[0101] Embodiment 5: Compared with Embodiment 1, the amount of glue applied is increased so that the glue accounts for about 11%, and the rest remains unchanged.
[0102] Example 6: Compared with Example 1, the ratio of the waterproofing agent to the binder is changed so that the mass of the binder is approximately 19 to 20 times the mass of the waterproofing agent, and the rest remains unchanged.
[0103] Example 7: Compared with Example 1, the ratio of the waterproofing agent to the binder is changed so that the mass of the binder is approximately 3 times the mass of the waterproofing agent, and the rest remains unchanged.
[0104] Example 8: Compared with Example 1, the type of binder is changed, and the rest remains unchanged.
[0105] Example 9: Compared with Example 1, the composition of the substrate is changed, and about 12% of organic synthetic fibers are added, while the rest remain unchanged.
[0106] Comparative Example 1: prepared according to existing reports as a control.
[0107] Comparative Example 2: A silicone resin filter material previously reported was used as a control.
[0108] It should be noted that Examples 1 to 9 are only preferred embodiments of the present invention and are not intended to limit the present invention. In other embodiments, the ratio of the waterproofing agent to the binder may be changed to make the mass ratio of the waterproofing agent to the binder greater than 1 / 3, or less than 1 / 20, thereby affecting the waterproofness, air permeability, bonding strength, structural stability, etc. of the filter material. Similarly, the amount of glue, the type of binder, and the composition of the substrate may also be adaptively changed according to actual needs.
[0109] Performance Testing
[0110] The test method for the performance index of the silicone resin modified filter material prepared above is as follows:
[0111] 1. Water seepage resistance (hydrostatic pressure resistance) test: Water seepage resistance is expressed by the hydrostatic pressure that the sample is subjected to before being penetrated by water, and is measured according to the American standard MIL-STD-282. Under the test conditions, one side of the sample is subjected to a continuous and uniformly increasing water pressure. According to the visual observation of water seepage, the water pressure value when water seepage occurs is the measured value of the water seepage resistance of the sample under the test conditions, expressed in Pa. Water seepage resistance can reflect the waterproof performance of the filter material.
[0112] 2. Failure test: The failure test is expressed by the test time and the retention rate of the sample's waterproof layer. In the failure test, the sample is first tested for its hydrostatic pressure resistance after preparation, recorded as X0, and then placed in a storage environment with a temperature of 20-25°C and a relative humidity of 45-65%. The hydrostatic pressure resistance of the sample is measured multiple times at fixed intervals, recorded as X1, X2, X3...X n . Hydrostatic pressure test value (X1, X2, X3...X n The retention rate of the sample waterproof layer is calculated by the ratio of the initial value of the hydrostatic pressure (X0) to the initial value of the hydrostatic pressure (X0), expressed in %. When the retention rate of the waterproof layer is ≤80%, the waterproof layer is considered to have failed. Failure test can reflect the durability of the filter material.
[0113] 3. Resistance and filtration efficiency test: Determined in accordance with GB / T 6165-2021 "High Efficiency Air Filter Performance Test Method Efficiency and Resistance" standard.
[0114] 4. Friction test: In the wear test, a weight of 200g is placed on the sample and pushed back and forth along the sample surface at a constant speed of 3cm / s on the coating machine to measure the water contact angle (WCA value) under different wear cycles (20 times, 40 times, 60 times and 80 times). For each sample, an average of five measurements are performed to determine the WCA value, and the volume of a single droplet is 5μL. The friction test can reflect the mechanical stability of the waterproof layer of the filter material.
[0115] The performance test results are shown in Table 3-4:
[0116] Table 3 Filter material performance test results
[0117]
[0118]
[0119] Table 4 Filter material performance test results
[0120]
[0121]
[0122]
[0123] Figure 1 The failure test results of the example samples and the comparative example samples are as follows: after storage for 168 hours (7 days), the filter materials of Examples 1-9 can still maintain 85-90% of the waterproof effect and have good durability, while the two comparative example samples have been reduced to below 45%.
[0124] Figure 2 The results of the hydrophobic effect of the sample in Example 1 and the comparative sample after multiple friction cycles: after 80 friction cycles, the filter material in Example 1 can still maintain a water contact angle close to 150° (a water contact angle greater than 150° is super hydrophobic), and the hydrophobic effect is good. The water contact angle of the comparative sample is already lower than 135°, which cannot meet the waterproof requirements.
[0125] Analysis of the mechanism of action of the reagents in the present invention
[0126] The structural fragment of formula (I) is usually found at the end and contains at least 3 R groups, which mainly play the role of end-capping and providing hydrophobic groups.
[0127] The structural fragments of formula (II) mainly play the role of providing hydrophobic groups and building a three-dimensional network structure. These structural fragments will form a chain structure (i.e., chain polysiloxane) when acting alone. The chain structure is entangled on the fiber surface, making it impossible for the hydrophobic groups to be evenly distributed; and the chain polysiloxane and the fiber are mainly bonded by intermolecular hydrogen bonds, and the stability of hydrogen bonds is poor and they are easily broken by environmental influences. Specifically, if the content of the structural fragments of formula (II) in the waterproof layer is high, the hydrophobic groups on the fiber surface are unevenly distributed, and the influencing factors in the environment (such as moisture, etc.) can begin to erode the waterproof layer from the part with less hydrophobic groups. The breaking of hydrogen bonds will further cause the waterproof layer to peel off from the fiber surface, resulting in failure points, which is manifested as a sharp decline in waterproof performance and insufficient durability after the filter material is stored in the natural environment for a period of time.
[0128] The structural fragments of formula (III) and formula (IV) are mainly responsible for building a three-dimensional network structure, in which there are fewer R groups that play a hydrophobic role. The number of hydrophobic groups in the network structure formed by these fragments alone is significantly smaller than the chain structure composed of the structural fragments of formula (II). If the content of the structural fragments of formula (III) and formula (IV) is high, the waterproof performance of the filter material is insufficient.
[0129] In the prior art, silicone resin waterproofing agents are commonly used to form a mesh structure. Common silicone resins are MQ silicone resins (i.e., most of the fragments of formula (I) and formula (IV)) that are obtained by polymerizing tetrafunctional monomers and then capping with monofunctional monomers. When used as a modified material for filter paper, the residual terminal hydroxyl groups of the MQ silicone resin can form a covalent bond with the surface of the fiber substrate, and solidify to form a hydrophobic layer with non-polar functional groups on the surface, so that the filter paper has hydrophobic and lipophilic properties. However, the hydrophobic layer mainly relies on the single effect of the residual terminal hydroxyl groups, and the bonding strength still cannot meet the use requirements in complex environments, and the durability and waterproofing effect are not ideal.
[0130] In the method of the present invention, a waterproofing agent is prepared by polymerizing a cross-linking monomer containing a structural fragment shown in formula (I), (II), (III), and (IV). After the auxiliary agent containing the waterproofing agent is applied to the substrate, the macromolecule containing the above structural fragment is attached to the surface of the substrate by physical adsorption, and gradually penetrates and wets the substrate, and the polymerized cross-linking monomer forms a three-dimensional network structure. During the drying and shaping process of the filter material, the active groups contained in the fragment can react with the groups on the fiber, and the structural fragment containing silicon hydroxyl Si-OH (i.e., the fragment where R is hydroxyl or R' is hydrogen) is hydrolyzed on the fiber surface and reacts with the functional group of the fiber to form a stable chemical bond connection (such as: Si-O-Si bond). R can also be selected from saturated groups and unsaturated groups. Saturated groups are preferably alkyl groups. The electronegativity difference between carbon and hydrogen in the alkyl group is small, and there is a stable covalent bond connection, low reactivity, and the saturated groups in the network structure tend to be arranged in agglomeration, thereby playing a hydrophobic effect; unsaturated groups are preferably alkenyl and alkynyl groups, which have high reactivity and can react chemically with groups (such as hydroxyl, carboxyl, ester, etc.) in the binder during the shaping process (which can be substituted, added or other mechanisms, especially added) to form a strong chemical bond connection, so that the waterproofing agent and the binder are effectively combined. During the preparation process, the waterproof layer is solidified on the surface of the filter material through the anchoring effect with the fiber and the binder, and it is not easy to fail.
Claims
1. A highly water-resistant and durable fluorine-free filter material, characterized in that: In terms of mass percentage, the components of the fluorine-free filter material include 77.0-96.8wt% glass fiber, 0-12.0wt% organic synthetic fiber, 3.0-9.5wt% binder and 0.2-1.5wt% waterproofing agent; Wherein, the waterproofing agent comprises structural fragments represented by formula (I), (II), (III) and (IV): In formula (I), (II), (III) and (IV), R is selected from one or more of hydrogen, hydroxyl, saturated group and unsaturated group; R' is selected from one or more of hydrogen, saturated group and unsaturated group, and the position of R' is a group or a chemical bond, and the chemical bond bonds the oxygen atom to any of the fragments of formula (I), (II), (III) and (IV).
2. The fluorine-free filter material according to claim 1, characterized in that: The saturated groups include: C1-C10 branched or straight chain alkyl groups, C3-C6 cycloalkyl groups, C1-C10 branched or straight chain alkoxy groups; Preferably, the saturated group is a C1-C6 branched or straight-chain alkyl group, a C1-C6 branched or straight-chain alkoxy group, and further preferably, the saturated group is selected from methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), methoxy (-OCH3), ethoxy (-OCH2CH3); The unsaturated groups include: C2-C10 branched or straight-chain alkenyl, C2-C10 branched or straight-chain alkynyl, C1-C10 branched or straight-chain acyl, C1-C10 branched or straight-chain acyloxy, phenyl, carboxyl, aldehyde; Wherein, the C1-C10 branched or straight-chain acyl / acyloxy group refers to: in the acyl / acyloxy group, except for the carbonyl (-C=O) / -COO, the remaining part is hydrogen (i.e., formyl, formyloxy), branched or straight-chain alkyl, branched or straight-chain alkenyl, branched or straight-chain alkynyl; Preferably, the unsaturated group is a C2-C6 straight-chain alkenyl group or a C2-C6 straight-chain alkynyl group; further preferably, the unsaturated group is a vinyl group (-CH=CH2) or an ethynyl group (-C≡CH).
3. The fluorine-free filter material according to claim 2, characterized in that: Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragment of formula (I) is 12.11% to 20.33%, the content of the fragment of formula (II) is 49.93% to 73.50%; the content of the fragment of formula (III) is 5.10% to 29.27%; the content of the fragment of formula (IV) is 0.85% to 9.92%; Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragments containing saturated groups is 61.46% to 70.91%; the content of the fragments containing unsaturated groups is 27.94% to 30.29%.
4. The fluorine-free filter material according to claim 3, characterized in that: Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragment of formula (I) is 17.11% to 17.22%, the content of the fragment of formula (II) is 63.91% to 65.81%; the content of the fragment of formula (III) is 14.02% to 14.63%; the content of the fragment of formula (IV) is 2.34% to 4.96%; Among all the fragments represented by formula (I), (II), (III) and (IV), the content of the fragments containing saturated groups is 66.84% to 68.62%; the content of the fragments containing unsaturated groups is 28.20% to 29.04%.
5. The fluorine-free filter material according to claim 2, characterized in that: The waterproofing agent is obtained by polymerizing a cross-linking monomer A, a cross-linking monomer B, a cross-linking monomer C, and a cross-linking monomer D. The cross-linking monomer A, the cross-linking monomer B, the cross-linking monomer C, and the cross-linking monomer D respectively contain structural fragments represented by formulas (I), (II), (III), and (IV).
6. The fluorine-free filter material according to claim 5, characterized in that: The crosslinking monomer A is trimethylethoxysilane, the crosslinking monomer B is dimethyldiethoxysilane, the crosslinking monomer C is vinyltriethoxysilane, and the crosslinking monomer D is tetraethoxysilane. When preparing the waterproofing agent, the molar ratio of the crosslinking monomer A, the crosslinking monomer B, the crosslinking monomer C and the crosslinking monomer D is 10-17.5:29-41:2-14:0.5-4, preferably 10.3-17.2:29-41:2.5-14:0.5-3.5 or 13-15:36-37:6-7:1.5-2.
0.
7. The fluorine-free filter material according to claim 1, characterized in that: The glass fiber is selected from micro glass fiber wool and glass fiber chopped strands; The organic synthetic fiber is selected from one or more of polypropylene fiber, polyester fiber, polyacrylonitrile fiber, polyamide fiber, polyimide fiber, and aramid fiber; The binder is selected from one or more of acrylic acid, polyurethane, vinyl acetate, and aluminum silicate; The fiber diameter of the micro glass fiber cotton is 0.1 to 5 μm, the fiber diameter of the glass fiber chopped strands is 5 to 10 μm; the fiber diameter of the organic synthetic fiber is 0.5 to 20 μm; The gram weight of the fluorine-free filter material is 10 to 200 g / m 2 ; Thickness is 0.1~10mm.
8. The fluorine-free filter material according to claim 7, characterized in that: In terms of mass percentage, the components of the fluorine-free filter material include 94.0-95.5wt% glass fiber, 4.0-5.0wt% binder and 0.5-1.0wt% waterproofing agent; In the glass fiber, the mass ratio of micro glass fiber wool with a diameter of 0.1 to 2 μm, micro glass fiber wool with a diameter of 2 to 5 μm, and glass fiber chopped strands is 4.5 to 5.5:1.5 to 2.5:1, preferably 5:2:1; The gram weight of the fluorine-free filter material is 67.27-73.82 g / m 2 ; Thickness is 0.45~0.55mm.
9. The method for preparing a fluorine-free filter material according to any one of claims 1 to 8, characterized in that: The steps include: S1. Select fiber raw materials according to proportion and prepare fiber substrate by wet papermaking process; S2, select waterproofing agent and adhesive in proportion and mix them evenly to prepare an aqueous solution with a concentration of 0.5-1wt%, which is a glue solution; S3, dipping or spraying the adhesive solution on the fiber substrate to obtain adhesive paper; S4. Dry the adhesive paper at a temperature of 100-120° C., and cure it at a temperature of 150-300° C. for 10-30 minutes to obtain a fluorine-free filter material.
10. The method for preparing a fluorine-free filter material according to claim 9, characterized in that: The waterproofing agent is prepared by cross-linking and polymerization of monomers containing structural fragments represented by formula (I), (II), (III) and (IV). The preparation method of the waterproofing agent comprises the following steps: Step A: Select a cross-linking monomer emulsion in proportion and place it in a reaction container, keep stirring at room temperature (20-25° C.), add 1-5% (based on the amount of monomer substance) of 10% dilute hydrochloric acid by mass, and stir at room temperature (20-25° C.) for 1-2 hours after the addition is completed to obtain a silanol solution; Step B: Add 5-10% (based on the mass fraction of monomers) of surfactant and 1-5V of deionized water into the reaction container, stir, add the above-mentioned silanol solution dropwise while maintaining room temperature, then heat to 80-120°C to react for 5-8h, cool naturally to room temperature, add 10-20% NaOH solution by mass to adjust the pH value to neutral, filter, and obtain a silicone waterproofing agent.
Citation Information
Patent Citations
Highly-resistant-to-water core-level glass fiber air filtering paper and preparing method
CN103243612B
Super-oleophylic and super-hydrophobic sponge for oil-water separation, and preparation method and application of super-oleophylic and super-hydrophobic sponge
CN110387062A
Filter media and articles inc.luding dendrimers and / or other components
CN102711948A
Epoxy / silicone polymer composite material, and preparation method and application thereof
CN102977553A
Highly-resistant-to-water core-level glass fiber air filtering paper and preparing method
CN103243612A
Cited By
Composite fluoride-free waterproof agent applied to glass fiber filter paper and preparation method of composite fluoride-free waterproof agent
CN120647847A